ЕСКИ УЙҒЫР ЖАЗЫЎЛЫ «ХУАСТУАНИФТ» ЕСТЕЛИГИ - Абдиназимов, Ш. (FAN va JAMIYAT, 2019)
The article is devoted to one of the Uyghur old manuscript monuments – «Huastuanift». It contains the Information about the manuscript versions of the monument. In the result of the investigation the author defined the word stock giving valuable information on the historical vocabulary of the Karakalpak language.